Thrombospondin-1 as a Paradigm for the Development of Antiangiogenic Agents Endowed with Multiple Mechanisms of Action - Marco Rusnati; Chiara Urbinati; Silvia Bonifacio; Marco Presta; Giulia Taraboletti (MDPI AG, 2010)
Uncontrolled neovascularization occurs in several angiogenesis-dependent diseases, including cancer. Neovascularization is tightly controlled by the balance between angiogenic growth factors and antiangiogenic agents. The various natural angiogenesis inhibitors identified so far affect neovascularization by different mechanisms of action. Thrombospondin-1 (TSP-1) is a matricellular modular glycoprotein that acts as a powerful endogenous inhibitor of angiogenesis. It acts both indirectly, by sequestering angiogenic growth factors and effectors in the extracellular environment, and directly, by inducing an antiangiogenic program in endothelial cells following engagement of specific receptors including CD36, CD47, integrins and proteoglycans (all involved in angiogenesis ). In view of its central, multifaceted role in angiogenesis, TSP-1 has served as a source of antiangiogenic tools, including TSP-1 fragments, synthetic peptides and peptidomimetics, gene therapy strategies, and agents that up-regulate TSP-1 expression. This review discusses TSP-1-based inhibitors of angiogenesis, their mechanisms of action and therapeutic potential, drawing our experience with angiogenic growth factor-interacting TSP-1 peptides, and the possibility of exploiting them to design novel antiangiogenic agents.